In silico identification and comparative analysis of molybdenum (Mo) transporter genes in plants - ÖZYİĞİT, İBRAHİM İLKER (SOC BOTANICA SAO PAULO, 2016)
Molybdenum (Mo) is an essential micronutrient element required by plants at trace amounts. Studies of Mo transporters mainly refer to the general characteristics of sulfate transporters because of limited knowledge about these proteins. In this study, we have identified 39 potential Mo transporter-like genes from 17 plant species by homology search. We report that Mo transporter proteins could be characterized with their Sulfate_transp and/or SUL1 protein domain family, 7-10 putative TMDs, basic characteristics, and mainly single exon number. In addition, we have searched the highly conserved residues in identified Mo sequences. These conserved residues could be used as potential motif signatures in identification of Mo transporter sequences. Phylogenetic analysis demonstrated a clear distinction between lower and higher plants in Mo transporter sequences. Despite some structural variations, general topological features of Mo transporters in higher and lower plants are not much divergent among 17 species. Identification of Mo transporter genes/proteins in various plant species, and their comparative analysis will provide valuable theoretical knowledge for future studies of better characterization of Mo transporters.
Keywords: Conserved domain; Molybdate; Motif signature; Transmembrane domain; COFACTOR BIOSYNTHESIS; MOLYBDATE TRANSPORTER; SULFATE TRANSPORTER; PREDICTION; PROTEINS; FAMILIES; DOMAIN